OP0306 Is there a Difference in the Presentation of Diffuse and Limited Subtype of Juvenile Systemic Sclerois in Childhood? Results from the Juvenile Scleroderma Inception Cohorte. www.juvenilescleroderma.com. (9th June 2015) - Foeldvari, I.; Katsicas, M.; Teresa Terreri, M.; Cimaz, R.; Kostik, M.; Sztajnbok, F.; Nemcova, D.; Moll, M.; Jose Santos, M.; Avcin, T.; Brunner, J.; Nielsen, S.; et al.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is an orphan autoimmune disease. Several publications in adults looked at the differences between limited and diffuse subtypes. There is rarity of data regarding this topic in pediatric jSSc. The juvenile scleroderma inception cohort (www.juvenilescleroderma.com ) is a prospective standardized register for patients with jSSc. Objectives: Comparison of features of patients with limited jSSc (ljSSc) and diffuse jSSc (djSSc) subtypes at the time of inclusion in the registry Methods: Patients with jSSc were included worldwide into the juvenile scleroderma inception cohort. We compared the demographics and clinical features of the ljSSc and djSSc. Results: Up till now 39 patients were enrolled, 29 with djSSc and 10 with ljSSc. 5 in the diffuse (17%) and 3 in the limited subtype (30%) had an overlap feature. The mean follow up of the patients in the cohort was 6.4 years in the djSSc and 5.3 years in ljSSc. 76% in the djSSc and 80% in the ljSSc group were female. The mean age at the onset of Raynaud's Phenomenon was 8.7 years in the jdSSc and 12.9 years in ljSSc group while the mean age at the onset of the first non-Raynaud presentation was 9.1years in djSSc and 13.8 years ljSSc. At the time of the inclusion the mean modified Rodnan Skin Score was 19.6 in the djSSc and 7.5 in ljSSc. 70% of patients in both groups had already capillary changes, but 67% in djSSc and only 33% in ljSSc had already history of ulcerations and 32.1% presented with active ulceration in the djSSc and none in the ljSSc. 72% of djSSc and 50% of ljSSc had cardiopulmonary involvement. The two patients with pulmonary hypertension had djSSc. 27.5% in djSSc and 30% in ljSSc group showed signs of interstitial lung disease on imaging. All 3 patients with renal involvement had djSSc. In both groups 30% had gastrointestinal involvement. Around 80% had musculoskeletal involvement in both subtypes. Anti-Scl 70 positivity was found in 40% of djSSc and 37.5% in ljSSc. Only 1 patient in the djSSc group had anticentromere antibody. Conclusions: We present the data on the first 39 patients with jSSc included in our cohort. Patients with djSSc and ljSSc differ in several characteristics. Patients with djSSc were younger at onset, had more often capillary changes and active ulcerations, pulmonary hypertension and renal involvement. The characteristics of the pediatric subtypes differs from adults with SSc. Disclosure of Interest: None declared